(untitled) (Journal of Engineering, 2010)
Construction projects contain many problems that can occur during the execution. Each problem results from many causes. Fault tree analysis (FTA) technique is a graphical model for analyzing causes of a problem (or undesired event) using logic gates to describe combinations of individual faults that can create an undesired event. Each level of the tree lists the lower level events that are necessary to cause the event shown in the level above it. The assessment process of a problem with FTA technique can be divided into two types: qualitative and quantitative assessment. As a case study to apply FTA technique in construction field, the researcher studied a building in Baghdad that had punching shear problem to analyze the causes lead to this problem. This research aims to introduce the main principles of FTA technique and how to use in identifying and analyzing the causes of problems that can occur in the construction projects. Also, it aims to compute the probability of occurrence of any problem or undesired event.